Holistic management of mobile energy storage fleets for more resilient service restoration - Yao, Shuhan (Nanyang Technological University, 2020)
The world economy continues to electrify. The power grid constitutes a vital cornerstone of critical infrastructures and serves as an essential foundation for the economy and society. Recent major blackouts caused by extreme weather events lead to catastrophic consequences. The impacts of extreme weather events pose unprecedented challenges to power grids and emphasize the importance of improving system resilience. It is indispensable to restore the electric service effectively in response to severe power outages, thus achieving more resilient distribution systems. When severe blackouts occur, a variety of local resources, e.g., microgrids and distributed energy resources, can be utilized to restore critical loads in distribution systems. Moreover, the emerging mobile energy storage systems (MESSs) can provide temporal-spatial mobility and coordinate with stationary local resources for an integrated distribution system restoration.